A case of non‐cardiogenic pulmonary edema provoked by intravenous acetazolamide. Issue 3 (24th April 2017) - Ono, Yuichiro; Morifusa, Makiko; Ikeda, Satoru; Kunishige, Chika; Tohma, Yoshiki
Abstract : Case: A 61‐year‐old man was diagnosed with severe chest trauma after a car accident and had had difficulty in weaning from a ventilator because of flail chest and dilated cardiomyopathy. On the 17th day in the intensive care unit, he received i.v. acetazolamide to increase urine output. One hour after the injection, he suddenly developed severe hypoxia. Chest radiography revealed a butterfly shadow. He received other diuretics and a vasodilator, which seemed slowly to resolve the respiratory failure. Five days later, acetazolamide was again given and he experienced the same deterioration. Outcome: We concluded that the episodes were attributed to pulmonary edema provoked by acetazolamide. Conclusion: Acute non‐cardiogenic pulmonary edema is an uncommon and lethal adverse effect of acetazolamide. Careful attention may be warranted when administering acetazolamide to critically ill patients. Abstract : Acetazolamide is a carbonic anhydrase inhibitor that is widely use in various clinical settings, although it is associated with rare episodes of potentially lethal adverse effects, such as non‐cardiogenic pulmonary edema. We report our experience with a critically ill patient who experienced two episodes of pulmonary edema after received acetazolamide.